2015
DOI: 10.1002/2015ja021066
|View full text |Cite
|
Sign up to set email alerts
|

First observations of poleward large‐scale traveling ionospheric disturbances over the African sector during geomagnetic storm conditions

Abstract: This paper presents first observations of poleward traveling ionospheric disturbances (TIDs) during strong geomagnetic conditions over the African sector. By analyzing different data sets we have observed both positive and negative ionospheric responses during the storm period of 08–10 March 2012. Considering the African region as a whole, three longitudinal sectors were strategically selected to establish the entire regional response. On both sides of the geomagnetic equator, results show poleward shift in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…TIDs originating from the geomagnetic equator during storms have been rarely reported, despite having been suggested and numerically shown by Chimonas [1969]. A link to direct observational evidence of poleward TIDs was recently presented in a region with sparse instrumentation over the low latitude region [Habarulema et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIDs originating from the geomagnetic equator during storms have been rarely reported, despite having been suggested and numerically shown by Chimonas [1969]. A link to direct observational evidence of poleward TIDs was recently presented in a region with sparse instrumentation over the low latitude region [Habarulema et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that JULIA daytime vertical velocities agree well with F-region Incoherent Scatter Radar (ISR) observations [Chau and Woodman, 2004], and JULIA data is therefore a reliable dataset to provide a picture of the local time electrodynamics over Jicamarca during the period under consideration. First observational results showing possible poleward TIDs were first reported by Habarulema et al [2015] over the African sector putting forward the dynamics of EEJ as the primary mechanism through Lorentz forcing. We wish to restate that possibilities of EEJ's role in driving poleward TIDS were first suggested and numerically shown by Chimonas [1969].…”
Section: Observations and Possible Driving Mechanismsmentioning
confidence: 99%
“…Several decades of ionospheric studies have shown that the ionospheric response to geomagnetic storms can differ above different locations (Yizengaw et al, 2005;Pirog et al, 2006a, b;Habarulema et al, 2013;Buresova and Lastovicka, 2017). Due to the relatively dense global coverage of Global Navigation Satellite System (GNSS) receivers, measurements of the total electron content (TEC) are nowadays used as a key parameter to study the ionospheric response to geomagnetic storms (e.g., Borries et al, 2016;Habarulema et al, 2015;Horvath and Lovell, 2015;Liu et al, 2016) and to describe an impact of the state of ionization of the Earth's upper atmosphere on the radio wave propagation conditions, which is crucial for terrestrial and Earth-space communications. The results of (Yin et al, 2004) demonstrated the potential of the two-dimensional tomographic methods extended to three-dimensional timedependent imaging and applied to ground based GPS observations, which allows GPS data to be used for large-scale studies of the ionosphere under very disturbed geomagnetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a growing number of studies that identify these poleward TIDs (e.g., Ding et al, 2013;Habarulema et al, 2015;Habarulema et al, 2017;Jonah et al, 2018;Zakharenkova et al, 2016, and references therein). However, there has been a growing number of studies that identify these poleward TIDs (e.g., Ding et al, 2013;Habarulema et al, 2015;Habarulema et al, 2017;Jonah et al, 2018;Zakharenkova et al, 2016, and references therein).…”
Section: Discussion and Summarymentioning
confidence: 99%